A quantum inspired MADM method and the application in E-commerce recommendation - Liu, Shuli (Technological and Economic Development of Economy, 2018)
In this paper, a quantum inspired MADM method is proposed. Inspired by quantum theory, the decision process is considered as a quantum probability system. Before the decision is made, the preference state is considered as the superposition from the sub-states with respect to various attributes. Each sub-state is regarded as the entanglement from the alternatives. Once the final decision is made, the preference state collapses into a definite state corresponding to an alternative. Based on the proposed method, the decision steps are provided. Ultimately, the feasibility is illustrated through an application in E-commerce recommendation.